Investigations in the strength of prestressed multilayered beams under the action of long-term shear/Medinių iš anksto įtemptųjų daugiasluoksnių sijų stiprumas veikiant ilgalaikėms skersinėms jėgoms - Čechavičius, Rimantas (Journal of Civil Engineering and Management, 1998)
The results of long-term experiments are presented in the paper. As a result of the experiments, invention SU 1025831 was developed under the name “The method of manufacture of a timber load-bearing element” (E 04 C 3/12, priority since July 11, 1981). The objective of the experiments performed was to check the method of increase of load bearing capacity of glulam beams under the influence of long-term shear. 14 beams were tested: nine of them were multilayered and 5 made of board-package and square-sawn timber. All the beams failed because of the action of shear forces. Two beams were tested by static short loading, the rest twelve by long-term loading. Three beams, that have not failed because of the action of long-term loading, then were tested by short-term loading. From the tests of multilayered, glulam and solid square-sawn timber beams the decrease of the relative strength wood split alongside fibres under the action of long-term shear is bigger than that given in literature in case of standard experiments. Relationship of the level of decrease of this strength with the duration of long-term loading may be calculated according to the Equation (2). The influence of long-term loading on the load-bearing capacity of these beams depends on the intensity of actions: if such a load does not cause the plastic deformations in the beam, their load-bearing capacity does not decrease and vice versa – the appearance of plastic deformations and micro-cracks means the decrease of load bearing capacity of the beam under a short-term shear. A short description of invention SU 1025831 is also presented in the paper. The invention is devoted to the perfection of the former invention No 954237. The latter one suggested an increase of load-bearing capacity of glulam elements under a short-term shear. Under a long-term load, or in case of fire, when the temperature and moisture around is changing, the strength of prestressed joint of these beams may not be fully guaranteed because of the influence of inner stresses and possible micro-cracking. With the purpose to increase the strength of beams under a long-term shear the author offers additionally to install pivots (Fig 6, 3) after giving prestress and full polymerisation. This method does not only increase the load-bearing capacity of multilayered elements under a long-term shear, but also ensures a higher reliability and fire resistance of such structures. Article in Lithuanian. First Published Online: 26 Jul 2012